Low birth weight and premature births and their associated maternal factors - Dayanithi, Mithila (International Journal Of Community Medicine And Public Health, 2018)
Background: LBW is a significant public health problem globally. In India every 3rd newborn is a LBW contributing to about 40% of the global burden. The objective of the study was to determine the prevalence of LBW and premature births and their associated maternal factors. Methods: A cross sectional study was done in antenatal women attending Rama Medical College Hospital& Research Centre, Hapur. Maternal factors and socioeconomic factors collected from 406 mothers were coded and analyzed using the SPSS 16. Chi square test was applied and p value less than 0.5 was considered as statistically significant. Results: Prevalence of LBW was 31.8% and prematurity was 25.6% in the study. LBW and premature babies were more associated with joint families, ≤Rs. 2999/- monthly income, maternal illiteracy and house wives. LBW and Premature babies decreased with increase in income, Hb >11.1 gms and ≥ 100 IFA tablets intake. The rates of LBW were the same whether mothers had no ANC or full ANC. This raises doubts about the content of the ANC. Conclusions: A good quality dedicated and sincere comprehensive ANC package including 4 ANCs, 100 IFA, 2TT/Booster, simple serial measurement of BP, weight, haemoglobin, fundal height and abdominal girth during each visit and screening for complications, counselling for birth and emergency preparedness, newborn care, breast feeding would help avert LBW and premature birth.